THE INFLUENCE OF DIGITAL MARKETING, TOURIST ATTRACTION, AND SERVICE QUALITY ON VISITOR LOYALTY WITH SATISFACTION AS A MEDIATING VARIABLE - Dede Yusuf Sutrisman; Abdul Kodir Djaelani; Ahmad Subhan Mahardani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study analyzes the influence of digital marketing, tourist attraction, and service quality on visitor loyalty at Eco Active Park, Batu City, East Java, with visitor satisfaction as a mediating variable. This research is motivated by the rapid growth of the tourism industry and increasingly intense competition, making visitor loyalty a crucial factor for business sustainability. Furthermore, the instability of visitor numbers reflects that visitor loyalty remains a major challenge that needs to be addressed by destination managers. The study employed a quantitative explanatory approach with a nonprobability sampling technique through purposive sampling involving 100 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results indicate that tourist attraction and visitor satisfaction have a positive and significant influence on visitor loyalty, as indicated by p-value of 0.000 and 0.001, respectively, while digital marketing and service quality do not have a significant direct effect, as indicated by p-value of 0.386 and 0.162. Furthermore, visitor satisfaction is proven to mediate the influence of digital marketing, tourist attraction, and service quality on visitor loyalty, as indicated by p-value of 0.023, 0.004, and 0.011, respectively. These findings affirm that visitor satisfaction is the key factor in building loyalty, which should be the top priority for long-term business sustainability